2010
DOI: 10.51724/ijpce.v2i1.116
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Age Study on the Understanding of Heat and Temperature

Abstract: The aims of this study were considered below under three headings. At these headings; the first was to elicit misconceptions that students had on the terms heat and temperature. The second was to understand how students’ prior learning affected their misconceptions. The third was to determine if students were able to make a connection between their own knowledge and physics in everyday life. To achieve these aims, a paper andpencil test composed of 14 multiple-chosen questions was designed, but only five quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 52 publications
(41 reference statements)
0
8
0
2
Order By: Relevance
“…Hal ini menunjukkan bahwa siswa masih mengalami kesulitan dalam memahami faktor-faktor yang dapat mempengaruhi perubahan suhu suatu benda. Siswa masih beranggapan bahwa suhu suatu benda tergantung pada ukuran benda (Budiarti et al, 2017;de Berg, 2008;Gönen & Kokaya, 2010).…”
Section: Metodeunclassified
See 1 more Smart Citation
“…Hal ini menunjukkan bahwa siswa masih mengalami kesulitan dalam memahami faktor-faktor yang dapat mempengaruhi perubahan suhu suatu benda. Siswa masih beranggapan bahwa suhu suatu benda tergantung pada ukuran benda (Budiarti et al, 2017;de Berg, 2008;Gönen & Kokaya, 2010).…”
Section: Metodeunclassified
“…Siswa beranggapan bahwa ketika suatu benda mengalami perubahan wujud, maka benda tersebut juga mengalami perubahan suhu (Maunah, 2014). Selain itu, siswa juga beranggapan bahwa ukuran benda dapat mempengaruhi suhu benda tersebut (Budiarti et al, 2017;de Berg, 2008;Gönen & Kokaya, 2010).…”
unclassified
“…On the other hand, based on the reasons given by students, we can categorize the understanding into sound understanding (SU), partial understanding (PU), partial understanding with specific misconceptions (PUSM), specific misconceptions (SM) and not understanding (NU) [14,15]. By categorizing student understanding, we will get more detailed information regarding the level of student understanding.…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed that students have various alternative conceptions and mental models that are not in line with scientific explanations. Studies in the other fields of science that applied cross-sectional approach include Coll & Treagust (2003), Gönen & Kocakaya (2010), Kurnaz & Eksi (2015), Lin (2017), Sahin et al (2008), Vosniadou & Brewer (1992), and Vosniadou & Ioannides (1998).…”
Section: Introductionmentioning
confidence: 99%